ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL PERSAMAAN GARIS LURUS BERDASARKAN TEORI NEWMAN DAN MINAT BELAJAR SISWA - Fitri Utami; Rippi Maya; Nelly Fitriani; Gida Kadarisma (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
This study aims to dissect the students’ errors in solving math essay-test using Newman’s error category and analyze the students’ learning interest in the straight-line equation. The exploration carried out utilizes the constructivist approach as well as a form of descriptive exploration. The subjects of this exploration are the 8th-grade students of SMP in Kabupaten Bandung Barat in the academic year 2021/2022. The device in this exploration is in the form of 4 questions which are analyzed using Newman's proposition and non-tests in the form of a student learning the interest scale conforming to 18 questions. Grounded on the results of data analysis, it was concluded that scholars made (1) errors in reading the question; (2) errors in learning the problem; (3) errors when transubstantiation the problem; (4) errors when procedural skills; and (5) writing errors in the final answer. The affair of this study proves that students' interest in learning the material of straight-line equations is included in the strong classification.